CLINICAL STUDY REPORT: AN OVERVIEW OF REGULATORY DOCUMENTS AND THE ORGANIZATIONAL AND PRACTICAL ASPECTS OF DEVELOPMENT - E. A. Radkova; I. N. Petrova; K. A. Leus; I. A. Dobromyslov (Разработка и регистрация лекарственных средств)
Clinical study report is one of the main documents during the drug development. The preparation of the clinical study report requires knowledge of Russian and foreign legislation, awareness of guidelines and recommendatioins issued by the professional associations as well as the effective process management. This article provides an overview of the current Russian and international regulatory documents and recommendations of professional organizations on the content and structure of the clinical study report, and describes an example of an algorithm for preparing the report from the earliest stages (data processing) to writing the final report with interpretation of study results.